2018
DOI: 10.3390/ma11122452
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Visible Light-Induced g-C3N4/Rectorite Composite for Efficient Photodegradation of Ciprofloxacin

Abstract: A novel kind of g-C3N4/rectorite composite with high visible-light photoactivity was developed via a mild and cost effective two-step process. Ciprofloxacin (CIP), a typical antibiotic, was applied to evaluate the photoactivity of the received catalysts. Furthermore, the by-products of CIP photodegradation were analyzed and the possible degradation pathways were also discussed. Compared with bare photocatalysts, the received composite possessed well reusability and higher photoactivity towards CIP. According t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…In contrast, the samples deposed on conductive substrates such as Ti_FTO (Figure 7) and Ti_Al (Figure 8) presented a similar kinetic mechanism during the entire photocatalytic period. This result confirmed that the production of the oxidative species during the photocatalytic process was significantly influenced by the substrate nature [37]. The kinetic data model for these two-interval reaction are included in Table 3 for the Apd pollutant and Table 4 for the Tr pollutant.…”
Section: Photocatalytic Propertiessupporting
confidence: 65%
“…In contrast, the samples deposed on conductive substrates such as Ti_FTO (Figure 7) and Ti_Al (Figure 8) presented a similar kinetic mechanism during the entire photocatalytic period. This result confirmed that the production of the oxidative species during the photocatalytic process was significantly influenced by the substrate nature [37]. The kinetic data model for these two-interval reaction are included in Table 3 for the Apd pollutant and Table 4 for the Tr pollutant.…”
Section: Photocatalytic Propertiessupporting
confidence: 65%
“…The main aim of this work is to predict maximum achievable [N] network in amorphous Si-B-C-N materials in a wide range of [Si]/[B]/[C] ratios. The background hypothesis, supported by the author’s previous works [ 30 , 41 ] on simpler nitrides and the discussion therein, is that maximum [N] network in those materials which are not affected by the composition and structure of their precursors is largely given by the formation of N 2 molecules during the atom-by-atom growth (not to be confused with polymerization of N-rich precursors such as melamine or dicyandiamide [ 42 ], which is beyond the present scope). Maximum [N] network calculated at numerous [Si]/[B]/[C] ratios is compared with experimental [N] total values obtained in our laboratory by reactive magnetron sputtering using equally numerous sputter target compositions.…”
Section: Introductionmentioning
confidence: 87%
“…A novel g-C 3 N 4 /rectorite composite was synthesized by Sun et al using a simple and low-cost method. They found that including rectorite reduced g-C 3 N 4 agglomeration, raised the surface area, and greatly enhanced the photocatalytic performance of the composite toward CIP degradation [80].…”
Section: G-c 3 N 4 /Rectoritementioning
confidence: 99%